A Biographical Analysis Of William Blake’s Poems - Khomsaton Dwi Mansoben (Leksikon: Jurnal Pendidikan Bahasa, Sastra, dan Budaya, 2023)
This research aims to find out whether the life of William Blake was reflected in his poems. The reason the author wants to analyze the poems and the biography of William Blake because the author found an interesting fact that Blake was said to be unschooled but he could make so many literary works. This is a descriptive qualitative research using a biographical approach and hermeneutic theory. Data sources are taken from 10 poems written by Blake, namely A Poison Tree, The Tyger, The Angel, London, The Little Boy Lost, The Lamb, The Little Boy Found, The Chimney Sweeper, The Land of Dreams, The Little Black Boy. The author collects data by applying documentary techniques with the following steps namely, First, the author finds or identifies the poems of William Blake. Second, the author selected the poems of William Blake in form random. Third, after the author selected the poem in form random, the author reads and understands the outline that these selected poems describes of William Blake's biography and to analyze the data, the author uses three steps namely: data reduction, display and conclusion drawing. The result of the analysis found that the ten poems written by William Blake reflect his life. All ten poems describe his anger at his enemies, his love for children and animals, his family, his home and his literary works. Thus, the author can conclude that in William Blake's life there are joys and sorrows, struggles, glory days, and getting his first vision in his biography.